1992
DOI: 10.1104/pp.100.4.1759
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Ethylene Inhibits Nodulation of Pisum sativum L. cv Sparkle

Abstract: Exogenous ethylene inhibited nodulation on the primary and lateral roots of pea, Pisum sativum L. cv Sparkle. Ethylene was more inhibitory to nodule formation than to root growth; nodule number was reduced by half with only 0.07 ML/L ethylene applied continually to the roots for 3 weeks. The inhibition was overcome by treating roots with 1 gM Ag', an inhibitor of ethylene action.Exogenous ethylene also inhibited nodulation on sweet clover (Melilotus alba) and on pea mutants that are hypernodulating or have ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 16 publications
(26 reference statements)
2
106
0
2
Order By: Relevance
“…Air was scrubbed of ethylene by passage through Purafil (Purafil Inc., Atlanta, GA) and pumped to a four-outlet manifold (Lee and LaRue, 1992). Ethylene was then added through micro valves (Nupro Co., Willoughby, OH) to three outlets to give concentrations ranging from 0.05 to 1.0 /iL L" 1 .…”
Section: Ethylene Application and Measurementmentioning
confidence: 99%
“…Air was scrubbed of ethylene by passage through Purafil (Purafil Inc., Atlanta, GA) and pumped to a four-outlet manifold (Lee and LaRue, 1992). Ethylene was then added through micro valves (Nupro Co., Willoughby, OH) to three outlets to give concentrations ranging from 0.05 to 1.0 /iL L" 1 .…”
Section: Ethylene Application and Measurementmentioning
confidence: 99%
“…In particular, the plant hormone ethylene (ET) has long been recognized as a negative regulator of the legume-rhizobial symbiosis (Lee and LaRue, 1992). ET acts at multiple symbiotic stages during nodule initiation, and many of ET's effects on symbiosis may be explained by negative regulation of Nod factor signaling, although the molecular mechanism(s) of such regulation is not understood.…”
mentioning
confidence: 99%
“…Earlier reports indicated that ethylene affects rhizobia induced nodulation both at the level of rhizobial infection 19 as well as nodule organogenesis. 25 For spontaneous nodulation, the signaling pathway originating from rhizobial infection is bypassed. This might explain why there is only 2-fold increase in spontaneous nodules in absence of rhizobia in skl background.…”
mentioning
confidence: 99%